Use of castor oil-based polyurethane adhesive in the production of glued laminated timber beams - Azambuja,Maximiliano dos Anjos (2006)
Researchers from the Polymer Technology and Analytical Chemistry (LQATP) group at the São Carlos Institute of Chemistry, University of São Paulo, developed a polyurethane adhesive based on castor oil. In addition to deriving it from a renewable source, this adhesive is nonaggressive to humans and the environment. The purpose of this study is to investigate the feasible use of polyurethane adhesive based on castor oil in the production of 12 beams of Glulam, using the species Pinus caribea hondurensis and Eucaliptus grandis. The structural performance of the beams of Glulam was evaluated through static bending tests. The results obtained enabled to conclude good efficiency of the polyurethane adhesive based on castor oil, for use in Glulam.